1970
DOI: 10.1063/1.1658395
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Electromigration-Induced Failure Time on Length and Width of Aluminum Thin-Film Conductors

Abstract: Experiments have been undertaken to determine the length and width dependence of electromigration-induced failure time in aluminum thin-film conductors. A statistical model is presented and compared to the experimental data. The significance of the experimental data and the statistical model are discussed in terms of randomly distributed structural defects which produce flux divergences during electromigration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(33 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…These results indicate that all the samples tested in this experiment have various microstructures and different defect densities depending on their positions on the substrate. 12 The MTTF and standard deviation for samples with 160 and 180°C of ambient temperatures had 3.47 ͑2.12͒, and 3.74 ͑1.74͒ h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that all the samples tested in this experiment have various microstructures and different defect densities depending on their positions on the substrate. 12 The MTTF and standard deviation for samples with 160 and 180°C of ambient temperatures had 3.47 ͑2.12͒, and 3.74 ͑1.74͒ h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…They showed that time to failure versus current density varied complexly, and that a simple power-law dependence (as shown by Black) was inadequate to describe the experimental conditions over more than a small range of current densities. The results of I Attardo [1970], Black (1968], and Blair [1970] were tangential to the results from the Venables and Lye model at a temperature of 210°C and current densities ranging from 1 x 104 A/cm 2 to 2 x 106 A/cm 2 (Figure 2.10). Venables and Lye [1972] showed that when the temperature dependence of times to failure due to electromigration was represented as an Arrhenius plot, although the curves appeared as accurate straight lines, the slopes yielded only apparent activation energy, which varied with test conditions, indicating that the time to failure was 3 a complex function of baseline temperature and could not be represented by an Arrhenius plot to give an activation energy (Figures 2.11 and 2.12).…”
Section: U Umentioning
confidence: 99%
“…Conversely, the accumulation 3 of mass occurs wherever the electron flow is in the direction of decreasing temperature [Venables and Lye 1972] [Venables and Lye 1972]. Electromigration in thin-metallized films is confined mainly to grain boundaries [Blech 1967, Agarwala 1970, Rosenberg 1968. Thus, the steady-state temperature dependence of electromigration is of the same magnitude as that of…”
Section: Steady-state Temperature Effects In the Presence Of Voidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliability models (Electromigration [5,7], Ohmic contact degradation [25,26], Coffin-Manson model [14], Eyring model [6,23,24], Humidity model [8], TDDB [15,16], Hot Carrier Injection [17,18], Hydrogen poisoning [9,[19][20][21], Thermo-mechanical stress [22], NBTI [23], etc…) are generally expressed by a function of stress parameter multiplying the exponential activation energy factor [10]. These expressions may not look much like a multiple-stress model but in fact it is as we have shown in paper presented at the 2013 IEEE Aerospace Conference [4]:…”
Section: Transition State Theory Applied To Reliability and Physics Omentioning
confidence: 99%